PERBEDAAN PERTUMBUHAN DAN PRODUKTIVITAS TANAMAN SAWI PAGODA MENGGUNAKAN PUPUK ORGANIK CAIR DARI ECENG GONDOK DAN LIMBAH SAYUR - Ria Dwi Jayati; Ivoni Susanti (Jurnal Biosilampari : Jurnal Biologi, 2019)
This study aims to determine the differences in the growth and productivity of the pagoda (Brassica narinosa) mustard fertilized using Eichornia crassipes and liquid vegetable organic fertilizer. The type of research used was an experiment with a complete randomized design (CRD) using 4 treatments and 6 replications. The respective treatments were: (P0) negative control, (P1) positive control, (P2) POC water hyacinth, and (P3) POC vegetable waste. The tools used in this study are: Polybags, small shovels, rulers, shovels, cameras, and buckets. The materials used in this study are: mustard pagoda plant seeds, vegetable waste, water hyacinth, EM4, NPK fertilizer, livestock manure, sugar, water and soil. This research is divided into two stages. The first stage is the process of making POC. The second stage is testing the effectiveness of POC on mustard pagoda plants. The results of the study data were analyzed by one-factor ANAVA using SPSS 16 and continued using the LSD test at the 5% level. The results showed that there was a difference in growth and productivity of mustard pagoda plants (Brassica narinosa) fertilized using water hyacinth (Eichornia crassipes) liquid organic fertilizer and vegetable waste liquid organic fertilizer and the best was found in P3 treatment (vegetable waste POC). Keywords: Organic fertilizer, Brassica narinosa, Eichornia crassipes